Pengaruh Monitoring Terhadap Kinerja Aparatur Sipil Negara (ASN) Terhadap Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Gowa - Andi Nur Intan Azizah Syamsuddin; Chalid Imran Musa; Abdi Akbar (Akuntansi, 2023)
This research aims to find out whether there is a significant positive influence on Monitoring the Performance of State Civil Apparatus (ASN). The research method used in this research is quantitative. The population in this study was 39 ASN at the Gowa Regency Personnel and Human Resources Development Agency (BKPSDM). Data collection techniques use observation, questionnaires and documentation techniques. The data analysis techniques used are simple linear regression analysis, coefficient of determination, and partial test (t). Based on the research results, simple linear regression results were obtained which showed the equation y= 22.20 + 0.497x The coefficient of determination (r2) for this factor has a value of 0.336 or 33.6%, the remaining 66.4% is influenced by other variables not included in this research model. This is proven by statistical tests showing that the t-value = 2.606 is greater than the t-table = 0.309. The calculation results obtained show that the monitoring variable has a positive and significant influence on ASN performance and the hypothesis results are acceptable.